Comparative Analysis of Filipino and Indonesian Monophthongs (Universitas Pamulang, 2020)
Filipino and Indonesian belong to the Austronesian language family and this explains why they exhibit many linguistic similarities and numerous cognates. This study aims to further compare the two languages and establish their connection through phonology. The researchers use the cognates to compare the Filipino and Indonesian monophthong vowels. Qualitative method is utilized. The result shows that Filipino and Indonesian have a very similar vowel system with the exception of Indonesian having /É™/ phoneme. It was also found out that most of the changes in monophthongs between the two languages appear in medial position. Moreover, most changes are from the mid back rounded vowel /o/ in Filipino to high back rounded vowel /u/ in Indonesian. Lastly, the changes in the unrounded vowels in Filipino usually appear in the initial and medial position whereas in the rounded vowels in Filipino, changes only appear in either the medial or final position.